Fund-Supported Programs and Crisis Prevention. (Policy Papers; Policy Paper, 2006)
This paper examines the theoretical foundations for, and empirical evidence of, Fund support in preventing capital account crises. At a theoretical level, Fund supported programs can lower the crisis probability in two ways. First, such programs provide the member with additional external reserves, making a run for the exit by private creditors less likely. Second, such programs induce and signal better economic policies, though this needs to be supported by conditionality.